Cidadania e educação ambiental: uma leitura do art. 225, §1º, VI/CRFB/88 e um olhar sobre a problemática ambiental brasileira. - Medeiros Júnior, José Flôr de (2019)
The present dissertation presents reflections on citizenship, environmental citizenship and environmental education built on the theoretical elaborations of Immanuel Kant and John Rawls. This is important to emphasize the need for new (re) actions in the face of the new philosophical, legal, political, economic, social, cultural and environmental conflicts due to the legal world and the imperative to rethink the theoretical constructions built in the territory of the Law from a deterritorialized look on established knowledge. In this way, we opted for the procedural paradigm with the aim of presenting a reading away from the substantialist paradigm and from the imprisonment of the interpretations constructed from the will of the State acting in its Hobbesian position residing in this. For this reason, when discussing citizenship, environmental citizenship and environmental education in the way they were thought by the original constituent and written in the Constitution of the Republic of 1988, we sought to distance ourselves from the state's will in relation to citizenship, environmental citizenship and education environmental. In the elaboration of this text we chose to seek to establish a dialogue where we could demonstrate the existence of a citizenship established in the legal plane dissociated from the historical-political-philosophical plane, away from citizenship in the condition of political practice. Citizenship ended, in our eyes, because it was so far removed from freedom, from the autonomy of the will, from the dignity of the human person, from equality, from political autonomy, and, finally, from the citizen himself. We seek, therefore, to distance ourselves from the legal-state aspect of citizenship by a citizenship in the condition of political practice. Because of this view, the construction of this path necessarily goes through the historical-philosophical-political-juridical discussion of what may or may not be termed as citizenship, provided that it establishes a new understanding regarding citizenship, environmental citizenship and environmental education.